Some Physical And Chemical Properties Of The Bioactive Components Responsible For Antinociceptive Activity Of Haruan (Channa Striatus) Extracts - Zakaria, Zainul Amiruddin (2001)
Haruan (Channa striatus) fillet and mucus extracts have been proven to exhibit a dosedependent antinociceptive activity and enhanced morphine effect. This current study is to establish some of the physical and chemical properties of the bioactive components responsible for haruan antinociceptive activity. Five types of solvents (water, methanol, ethanol, chloroform and chloroform:methanol) were used to extract the respective components from freeze-dried haruan fillet. Various salts (NaCI, K Cl, CaCh, MgCh and their combinations (MS» were used to study the involvement of ionic components in mediating the antinociceptive activity of haruan extract. The aqueous portion obtained after a chloroform:methanol extraction of fresh haruan fillet was filtered using three types of Millipore filters (30,000, 10,000 and 5,000 Nominal Molecular Weight Limit (NMWL), respectively. Lastly, the aqueous portion, filtered using the 5,000 NMWL Millipore filters, was purified using the High